Corrosion and Precipitation Study of Rasht’s Water Supply Resources - Ramezani, Parvin (Asian Journal of Chemistry, 2010)
Water and wastewater should not corrode the structures, fitting or mechanical equipment with which they come in contact. Aggressive water is drinking water that can cause corrosion. It is a real and growing problem in many parts of the country. Leaks are developing in new homes that are less than 2 years old in some cases. These leaks can cause high water bills and structural damage. Home-owners or municipal water systems that obtain their water from wells are susceptible. The causes and mechanisms that are responsible for the corrosion are not always the same. Water that is slightly acidic is responsible for the corrosion. High levels of dissolved minerals and carbon dioxide can also cause problems corrosion and precipitation effect of Rasht's water supply resources are studied. The qualitative and quantitative experiments such as pH, dissolved oxygen , CO2, TDS, temperature, alkalinity, etc. are done during two hydrological years 1997-1999. Water from the stations Otobosrani (O), Seateh (Δ), Helale Ahmar (⌀), Razi Hospital (*), Khachekin (☺), Shalco (☀) , and Shagaji (□) are not corrosive, but Emamzadeh Hashem (■) is corrosive and treated water (Φ) after treatment of raw water (●) is corrosive in cold water pipes.